Odpowiedzi

2010-03-15T15:25:29+01:00
(6x - 2y ) :2 = 3x-y
(-3a - 1 1/2 ) : (-3) = a+0,5
(2,4a - 1,6b) : (1/5) = 12a-8b
(4u - 6v) : (-1/5) = 20u+30v
2010-03-15T15:41:09+01:00
(6x - 2y ) :2
[(2*3)x - (2*1)y] :2
[2(3x-y)]:2
3x-y

(-3a - 1 1/2 ) : (-3)
[(-3*1)a + (-3*1/2)] : (-3)
-3[a+1/2] : (-3)
a + 1/2

(2,4a - 1,6b) : (1/5)
[(12/5)a - (8/5)b] : (1/5)
[(1/5 *12)a - (1/5* 8)b] : (1/5)
[1/5(12a - 8b)] : (1/5)
12a-8b

(4u - 6v) : (-1/5)
[(20/5)u - (30/5)v] : (-1/5)
[((-1/5)*(-20))u + ((-1/5)*30)v] : (-1/5)
-20u + 30v